Partial purification and characterization of molybdenum reducing enzyme from Escherichia coli strain K12 - Sulaiman, Mohd Haris (2015)
Molybdenum is becoming a threat to environment due to its toxic effect in high concentration due to various industrial use. Therefore improper management of this heavy metal waste will cause it to remain in the ecosystem. To date, the best way to treat heavy metals is via bioremediation. Escherichia coli (E. coli) have been reported to have the capability to reduce the heavy metal molybdenum (molybdate) to molybdenum blue. Thus, this study was conducted to determine the optimum environmental and nutrient conditions of Escherichia coli strain K12; to partially purify molybdenum reducing enzyme; and to characterize the molybdenum reducing enzyme. E. coli are Gramnegative bacteria that belong to the g-proteobacteria. They exist in a straight rod shaped cells and about 2 μm long and 0.5 μm wide, which can grow and divide rapidly by binary fission. In this experiment, E. coli was used to reduce molybdate Mo6+ forming a Moblue with the aid of Molybdenum reductase (Mo-reducing enzyme) which give non-toxic effect to the environment. Bacteria were cultured in a low phosphate media, pH 7.5 at temperature 35°C and incubated for 2 days. The optimization studies were carried out to optimize the production of molybdenum blue. The combination of 1% (w/v) glucose,0.4% (w/v) ammonium chloride, 0.2% (w/v) yeast extract, and in ratio of 5mM phosphate and 80mM molybdate at pH 7.5 gave the optimum production of Molybdenum blue. Based on the maximum absorption peak at 865nm, this wavelength was used for the measurement of molybdenum blue produced in subsequent experiments. The effect of heavy metals on molybdenum blue production were studied. Thirteen metal ions and heavy metals were screened on E.coli. Mercury (Hg), Argentum (Ag), Copper (Cu) and Chromium (Cr) totally inhibited molybdate reductase enzyme while Zink (Zn), Nickel (Ni), Cobalt (Co), Arsenic (As), Lead (Pb) Aluminium (Al), Cadmium (Cd), and Magnesium (Mg) decreased the molybdenum reduction activity. Partial purification and characterization were conducted on molybdenum reducing enzyme with anion exchange chromatography using GE-Healthcare Mono-QTM column and gel filtration chromatography using Agilent ZorbaxTM (GF-250) column. Two bands were visualized on the gel filtration fraction at 95.64 and 84.42 kDa using SDS polyacrylamide-gel electrophoresis (SDS-PAGE). In enzyme kinetic studies, characterization of enzyme and stability of enzyme is being studied. NADH serves as the substrate for electron donor and 12-Molybdophosphate act as the substrate. The Km and Vmax for NADH were 2.156 mM and 15.015 units/ mg enzyme respectively. While the values for 12-MP were 3.549 mM and 54.348 units/ mg enzyme respectively. The characterization of Mo-reducing enzyme studies were carried out at optimum pH of 6.0 using phosphate buffer at 35 ºC. For enzyme temperature stability, enzyme are stable at range of 5ºC - 40 ºC for a period of 24 hours. Based on the result obtained, Escherichia coli strain K12 was proven to be effective for reduction of molybdate forming molybdenum blue.